Stereotactic body radiation therapy with optional focal lesion ablative microboost in prostate cancer: Topical review and multicenter consensus. (November 2019) - Draulans, Cédric; De Roover, Robin; van der Heide, Uulke A.; Haustermans, Karin; Pos, Floris; Smeenk, Robert Jan; De Boer, Hans; Depuydt, Tom; Kunze-Busch, Martina; Isebaert, Sofie; Kerkmeijer, Linda
Highlights: SBRT represents a valid treatment option for men with low/intermediate risk PCa. Adding a focal boost to the intraprostatic tumor may improve disease control. A focal boost might have favourable toxicity compared to whole-gland dose-escalation. Currently, SBRT with a focal boost for PCa should be restricted to clinical trials. Abstract: Stereotactic body radiotherapy (SBRT) for prostate cancer (PCa) is gaining interest by the recent publication of the first phase III trials on prostate SBRT and the promising results of many other phase II trials. Before long term results became available, the major concern for implementing SBRT in PCa in daily clinical practice was the potential risk of late genitourinary (GU) and gastrointestinal (GI) toxicity. A number of recently published trials, including late outcome and toxicity data, contributed to the growing evidence for implementation of SBRT for PCa in daily clinical practice. However, there exists substantial variability in delivering SBRT for PCa. The aim of this topical review is to present a number of prospective trials and retrospective analyses of SBRT in the treatment of PCa. We focus on the treatment strategies and techniques used in these trials. In addition, recent literature on a simultaneous integrated boost to the tumor lesion, which could create an additional value in the SBRT treatment of PCa, was described. Furthermore, we discuss the multicenter consensus of the FLAME consortium on SBRT for PCa with a focal boost to the macroscopic intraprostatic tumor nodule(s).